Penggunaan Buku Ajar Fisika Berbasis Contextual Teaching and Learning (Ctl) untuk Meningkatkan Hasil Belajar & Aktivitas Siswa pada Pokok Bahasan Suhu dan Kalor - Endang Lovisia; Tri Ariani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
Abstract: The purpose of this study was to determine the effectiveness of the use of physics textbooks based on Contextual Teaching and Learning (CTL) to improve student physics learning outcomes on the Material of Temperature and Heat. The implementation design uses a pre-experimental design with One-Group Pretest-Posttest Design. The subjects of this research trial were all students of class XI IPA 1 SMA Negeri 5 (Model) Lubuklinggau. The n-gain test was conducted to determine how much improvement in student learning outcomes was after implementing Contextual Teaching and Learning (CTL) based physics textbooks. Data were collected by using questionnaires and test techniques. The activity of students has increased by 72.86% in the good category. The daily test results given >75% of students scored more than 70 of the seven questions given. The value of table with degrees of freedom (DK) = n-1 = 34-1 = 33 and = 0.05 count = 36.87 and table = 2.04 because count table. In conclusion, the use of the Contextual Teaching and Learning (CTL) model effectively improves students' physics learning outcomes. Keywords: Student Activities, Physics Textbooks Based on Contextual Teaching and Learning (CTL), Learning Outcomes